Дослiдження адсорбцiї молекули вуглекислого газу на графенi методом функцiонала щiльностi - Thakur, D. P.; Barde, N. P.; Bardapurkar, P. P.; Khairnar, R. S. (Publishing house "Academperiodika", 2018)
The physisorption of a CO2 molecule on a graphene sheet using ab initio density functional theory is investigated. The geometrical structure of graphene, including various parameters viz. the bond lengths and bond angles are calculated for a graphene sheet under the adsorption of a CO2 gas. Additionally, the density of states of a graphene sheet is calculated with & without adsorption of CO2 molecules. It is observed that the CO2 molecule is adsorbed on the graphene sheet with the adsorption energy of about 61.7 meV or less. The HOMO-LUMO energy levels of the graphene sheet before and after the adsorption of a CO2 molecule remain unaltered. Therefore, the graphene sheet cannot detect a CO2 molecule owing to their weak interaction.